PENINGKATAN KOMPETENSI PENDIDIK MELALUI PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN CHATBOT ACITA - Amy Krisdiana; Asih Andriyati Mardliyah (Jurnal Pengabdian Pada Masyarakat Indonesia, 2022)
In the 4.0 and 5.0 era, as an educator, we are required to use technology- based media in the form of web, digital platforms, and certain applications that assist educators in delivering material. Many technology-based media are used by educators, one of which is Chatbot. Chatbot is a computer program that can communicate (having conversation) like humans via internet. The objectives of this service activity are 1) to increase teacher knowledge about technology-based learning media materials; 2) equipping skills to participants (educators) so that they can create their own chatbot. The target partners involved were 32 participants who were divided into 8 groups, but only 20 participants were able to complete chatbot, which was then divided into 5 groups which the participants consisting of teacher, lecturers, university students, and even high school students. The approach method in this service activity is in the form of training through google meet and WhatsApp group. The result of the activity is that participants can create their own chatbot to the theme that the participants want.